Is the lack of response of maize to fertilization in soils with low Bray1-p related to labile organic phosphorus? - Appelhans, Stefania Carolina; Barbagelata, Pedro Anibal; Melchiori, Ricardo Jose; Gutierrez Boem, Flavio Hernán (Springer, 2021)
The usual soil test phosphorus (P) neglects the P supply from labile organic P (Po) fractions, which could explain the nonresponse of maize (Zea mays L.) in sites with soil P testing below the critical level. We aim to determine Po and inorganic P (Pi) in NaHCO3 extracts and in the coarse soil fraction (hereinafter, CF) from responsive and nonresponsive sites to P fertilization in maize. We then compare the classification errors of the Cate and Nelson method by comparing the relationship between maize relative yield and the soil Bray1-P concentration vs. the new proposed indices. The study included responsive and nonresponsive sites to P fertilization carried out across the Pampas Region in the center-east of Argentina. Treatments included four P fertilization rates: 0, 12, 24, and 36 kg P ha−1. The experiments were laid out in a randomized complete block design with three replicates. We determined Bray1-P, Pi, and Po in NaHCO3 extracts and in the coarse soil fraction. Sites non-responsive to P fertilization and with Bray1-P concentrations below the critical level showed 70% more Po in the coarse soil fraction (Po-CF) than sites with high crop response and similar Bray1-P level. However, Po-Bic alone did not improve the relationship with maize relative yield. Po-CF and Bray1-P included in a soil integrative P index improved the prediction of crop response to P fertilization and reduced classification errors, which suggests that Po-CF is a source of available P for the crops. The novelty reported in this study was to demonstrate the organic P contribution to relative yield by including it into an integrative soil testing. We find that nonresponsive sites to P fertilization, with low Bray1-P, were correctly classified when including Po-CF in a new soil test P. Improvements in the P fertilization diagnostic prescription tool contribute to an increase in economic profit and reduce environmental impact.